PEDAGOGICAL ASPECTS OF THE USE OF EDUCATIONAL VALUES IN THE SPIRITUAL DEVELOPMENT OF STUDENTS - Ziyayev A.N. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article is covered by teaching the science of the history of pedagogy by interpreting the pedagogical aspects of the use of educational values in the development of spiritual perfection in the student youth.Also,the relevance, conclusion and recommendations of the problem posed in it are relevant.